Axiological concept of LAZINESS as an object of linguistics and psychology - Lili Wang (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
Modern linguistics is a polyparadigmatic science, which is distinguished, in particular, by its interest in the data of psychology. It is especially important to involve the results of psychology during the study of axiological concepts, since it must be taken into account that the assessments made by people do not always have sufficient grounds. The purpose of the research is to consider the concept of LAZINESS from the point of view of various sciences, in particular cognitive linguistics and psychology, supplementing the linguistic data with knowledge about the causes of the studied condition.